Seasonal variation of the essential oil from two Brazilian native Aldama La Llave (Asteraceae) species - OLIVEIRA,TUANE S. DE (2016)
ABSTRACT Aldama arenaria and A. robusta are morphologically similar aromatic species that have seasonal development. The yield and chemical composition of essential oils from aerial and underground vegetative organs of these species were compared to verify the production of volatile metabolites in flowering and dormant phases of development and to identify if there are unique compounds for either species. The major compound in the essential oils from A. arenaria leaves was palustrol (16.22%) and for aerial stems was limonene (15.3%), whereas limonene (11.16%) and α-pinene (19.64%) were the major compounds for leaves and aerial stems from A. robusta, respectively. The major compound for the underground organs was α-pinene, in both species and phenological stages. High amounts of diterpenes were found especially for A. arenaria essential oils. Each analyzed species presented unique compounds, which can provide a characteristic chemical profile for both species helping to solve their taxonomic problems. This study characterized for the first time the yield and essential oil composition of A. arenaria and A. robusta, which have medicinal potential, and some of the compounds in their essential oils are unique to each one and may be useful in helping the correct identification of them.